Improving communication - Osborn, Suzanne; Motley, Michael T. (1999)
This mainstream, skills-oriented text helps students become competent communication receivers as well as senders. The text emphasizes public speaking and interpersonal communication skills with minimal theory, and includes a full seven chapters on public speaking. Addressing contemporary issues such as gender, ethics, and intercultural communication, Improving Communication examines the challenges these issues present in various areas of interpersonal, small group, and public communication.